The Impact of the Explosive’s Energy on Shovel Diggability in an Open Pit Gold Mine - Paulo Couceiro; Juan Navarro (International Society of Explosives Engineers, 2025)
The impact of rock blasting fragmentation and heave on digging performance in open-pit mining operations is usually the first true indicator of blasting outcomes. Within the typical excavation cycle, the bucket loading time or instantaneous digging rate are the ones that present the strongest correlation with rock fragmentation size distribution, swelling, and shape of the muckpile, a part of rock mass hardness, equipment size, power, and others. As the efficiency of unit operations becomes increasingly important for long-term mining strategies, cost-effective approaches are needed to increase mine productivity. In this line, the performance of downstream operations, such as digging, hauling, and comminution, may be affected by the energy input in blasting. This requires a better understanding of the explosive’s energy role in such unit operations in order to drive consistent improvements. Therefore, this paper examines the impact of the explosive’s energy distribution on shovel diggability from production shots carried out with different explosives in an open pit gold mine, with the aim of modelling the interface between blasting and excavation.